Cardinal parameter meta-regression models describing Listeria monocytogenes growth in broth. (October 2020) - Nunes Silva, Beatriz; Cadavez, Vasco; Teixeira, José António; Ellouze, Mariem; Gonzales-Barron, Ursula
Graphical abstract: Highlights: Cardinal values can be estimated by meta-analysing literature growth data. The meta-regression models built provide an insight on sources of variability. The cardinal values obtained can be used as reference values for risk assessments. Abstract: Since Listeria monocytogenes has a high case-fatality rate, substantial research has been devoted to estimate its growth rate under different conditions of temperature, pH and water activity (aw ). In this study, published findings on L. monocytogenes growth in broth were extracted and unified by constructing meta-regression models based on cardinal models for (i) temperature (CM[T]), (ii) temperature and pH (CM[T][pH]), and (iii) temperature, pH and aw (CM[T][pH][aw ]). After assessing all the sources retrieved between 1988 until 2017, forty-nine primary studies were considered appropriate for inclusion. Apart from the modelling variables, study characteristics such as: type of broth (BHI, TSB, TPB), reading method (colony-forming-units, CFU; or binary-dilution optical density methods, OD), inoculum concentration and strain serotype, were also extracted. Meta-regressions based on CM[T] and CM[T][pH] were fitted on subsets of the 2009 growth rate measures and revealed that type of broth and reading method significantly modulated the cardinal parameter estimates. In the most parsimonious CM[T][pH][aw ] meta-regression model, whereby the variability due to type of broth was extracted in a nested random-effects structure, the optimum growth rate μ opt of L. monocytogenes was found to be lower when measured as CFU (0.947 log CFU/h; SE = 0.094 log CFU/h) than when measured as OD (1.289 log CFU/h; SE = 0.092 log CFU/h). Such a model produced the following cardinal estimates: T min = -1.273 °C (SE = 0.179 °C), T opt = 37.26 °C (SE = 0.688 °C), T max = 45.12 °C (SE = 0.013 °C), pH min = 4.303 (SE = 0.014), pH opt = 7.085 (SE = 0.080), pH max = 9.483 (SE = 0.080), aw min = 0.894 (SE = 0.002) and a w opt = 0.995 (SE = 0.001). Integrating the outcomes from numerous L. monocytogenes growth experiments, this meta-analysis has estimated pooled cardinal parameters that can be used as reference values in quantitative risk assessment studies.